2018
DOI: 10.3168/jds.2017-13180
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of calcium hydroxide-treated corn stover as a partial forage replacement in diets for lactating dairy cows

Abstract: Chemical treatment may improve the nutritional value of corn crop residues, commonly referred to as corn stover, and the potential use of this feed resource for ruminants, including lactating dairy cows. The objective of this study was to determine the effect of prestorage chopping, hydration, and treatment of corn stover with Ca(OH) on the feeding value for milk production, milk composition, and dry matter intake (DMI). Multiparous mid-lactation Holstein cows (n = 30) were stratified by parity and milk produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Aines (1985) observed that pretreating wheat straw with 4% or 8% Ca(OH) 2 and feeding 90% wheat straw diets did not have an effect on solid or liquid passage rates; however, Oliveros et al (1993) similar to present study noted that even though solid passage rate was not affected, liquid passage rate was increased when corn stover in 90% corn stover diets was pretreated with 40 g/kg of Ca(OH) 2 . In addition, Casperson (2017) observed that replacement of a portion of haylage and corn silage with 9.6% of the diet DM as corn stover pretreated with 6.2% Ca(OH) 2 did not affect solid passage rate but increased liquid passage rate in lactating dairy cows. Increased liquid passage rate as a result of alkaline treatment indicates that more soluble nutrients were carried to the small intestine for digestion.…”
Section: Discussionmentioning
confidence: 97%
“…Aines (1985) observed that pretreating wheat straw with 4% or 8% Ca(OH) 2 and feeding 90% wheat straw diets did not have an effect on solid or liquid passage rates; however, Oliveros et al (1993) similar to present study noted that even though solid passage rate was not affected, liquid passage rate was increased when corn stover in 90% corn stover diets was pretreated with 40 g/kg of Ca(OH) 2 . In addition, Casperson (2017) observed that replacement of a portion of haylage and corn silage with 9.6% of the diet DM as corn stover pretreated with 6.2% Ca(OH) 2 did not affect solid passage rate but increased liquid passage rate in lactating dairy cows. Increased liquid passage rate as a result of alkaline treatment indicates that more soluble nutrients were carried to the small intestine for digestion.…”
Section: Discussionmentioning
confidence: 97%
“…Then samples were pooled, dried at 65°C for 48 h and grounded to pass through a 0.42-mm sieve. The macronutrient levels of the natural pasture were analyzed (Casperson et al, 2018) and showed as follows (air-dry basis): 4.81% crude protein (CP), 2.52% ether extract (EE), 55.01% neutral detergent fiber (NDF), 36.59% acid detergent fiber (ADF), 10.11% ash. Yaks in the GRB, GRBC and GRBY groups were housed in 15 pens according to treatment, with 2 yaks in each pen (3.5 × 8.0 m).…”
Section: Methodsmentioning
confidence: 99%
“…The chemical treatment of agricultural by-products has been extensively researched to improve the nutrient value of low-quality livestock feeds [22,23]. The disruption of lignin structures in agricultural residues and the rise in cellulose and hemicellulose are crucial for ruminant livestock diets [24]. This study compared the addition of Ca (OH)2 during fermentation and lowered the NDF, ADF, and ADL contents by 18%, 15%, and 27%, respectively, with EOPF (Table 1).…”
Section: Chemical Compositions Of Oil Palm Fronds Ensiled With Various Additivesmentioning
confidence: 99%